Convergence of Generalized Quasi-Nonexpansive Mappings in Hyperbolic Space. (14th June 2022) - Saleem, Naeem; Rashid, Maliha; Jarad, Fahd; Kalsoom, Amna
Abstract : In this article, we consider a wider class of nonexpansive mappings (locally related quasi-nonexpansive) than monotone nonexpansive mappings. We obtained the convergence of fixed point for quasi ϱ -preserving locally related quasi-nonexpansive mappings in hyperbolic space. An iterative process is also used to obtain the convergence results for this mapping. Fixed point is approximated numerically in a nontrivial example by using Matlab.